Public Service Agency: Business-Based Innovation in Public Institutions : (Study of Design of Government Institutions in The Field of Communications And Informatics) (Open Society Conference, 2023)
Legal certainty as a result of the development of laws and regulations encourages the establishment of the Regional Public Service Agency. By taking into account the principles of fairness, propriety, and benefits that are in line with Healthy Business Practices, BLUD seeks to provide public services more effectively, efficiently, economically, transparently, and responsibly. This will help achieve the goals of the regional government, whose management is carried out in accordance with the authority granted by the regional head. The purpose of this study is to serve as a document that can be used as a reference and considered in making policies related to the establishment of the Regional Public Service Agency in related institutions. The study was carried out by means of Value Proposition Analysis, focus group discussions, and an analysis of the hierarchy process. The results of the study recommend 12 Public Service Recommendations in the Field of Communication and Informatics, namely Application Development Services, Key Location Servers, Internet Services, Information Technology Architecture Development Services, Smart City Replication Services, Digital Content Creation Services, Advertising Services, Data Analysis Services, Consulting and Development Services HR, Dissemination Services, Research Services, and Report Preparation Services These service recommendations can be used as BLUD services that can be offered as a community